Notes on Distribution of Capparis rotundifolia Rottler (Capparaceae) - in Southern India - Ravikumar, K.; Udayan, P. S.; Subramani, S. P. (Indian Forester, 2004)
Capparis rotundifolia Rottler is distributed in India, Burma and Sri Lanka. In India, it is restricted to the peninsular region. The taxonomy, ecology and distribution of this taxon are discussed in detail for a better understanding of this uncommon species.